Common malaria Mosquito Anopheles quadrimaculatus Say (Insecta: Diptera: Culicidea): EENY 491/IN791, 2/2009 - Rios, Leslie M.; Rutledge-Connelly, C. Roxanne (EDIS, 2009)
EENY-491, a 6-page illustrated fact sheet by Leslie M. Rios and C. Roxanne Connelly, describes this historically most important vector of malaria in the eastern United States — synonymy, distribution, description, life cycle, medical significance, surveillance, and management. Includes selected references. Published by the UF Department of Entomology and Nematology, February 2009. EENY 491/IN791: Common Malaria Mosquito Anopheles quadrimaculatus Say (Insecta: Diptera: Culicidae) (ufl.edu)